Identification of high-risk patients for development of type B aortic dissection based on novel morphological parameters - Li, Da; Wang, Jiarong; Zhao, Jichun; Wang, Tiehao; Zeng, Xiangguo; Zheng, Tinghui; Yuan, Ding (Frontiers in Physiology, 2023)
Background: Predicting the development of sporadic type B aortic dissection (TBAD) always remains a difficult issue. This study aimed to identify high-risk patients for development of TBAD based on morphological parameters. Methods: This propensity-score-matched case-control study collected and reconstructed the computed tomography angiography of acute TBAD patients and hospital-based control participants without aortic dissection from January 2013 to December 2016. Multivariate regression analysis was used to calculate the adjusted odds ratio (aOR) and 95% confidence interval (CI). Discriminant and reclassification abilities were compared between our model and a previously established model. Results: Our study included 76 acute TBAD patients and 79 control patients (48 cases and 48 controls after propensity-score matching). The degree of question mark (aOR 1.07, 95% CI 1.04–1.11), brachiocephalic trunk diameter (aOR 1.49, 95% CI 1.20–1.85), brachiocephalic trunk angle (aOR 0.97, 95% CI 0.94–0.99), aortic root diameter (aOR 1.31, 95% CI 1.15–1.48), and aortic width (aOR 1.12, 95% CI 1.07–1.17) were associated with a significantly increased risk of TBAD formation. Similar findings were observed in the propensity-score matching and sensitivity analysis only including hyperacute TBAD patients. A novel prediction model was established based on the aforementioned parameters. The new model showed significantly improved discriminant ability compared with the previously established model (c-index 0.78 [95% CI 0.71–0.85] vs. 0.67 [95% CI 0.58–0.75], p = .03), driven by increased reclassification ability in identifying TBAD patients (NRI for events 0.16, 95% CI 0.02–0.30, p = .02). Conclusion: Morphological predictors, including the degree of question mark, aortic width, aortic root diameter, brachiocephalic trunk angle, and brachiocephalic trunk diameter, may be used to identify patients at high risk of TBAD.